2021
DOI: 10.1177/0954409721991309
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the marginal maintenance cost of different vehicle types on rail infrastructure

Abstract: In this paper, we combine engineering and economic methods to estimate the relative maintenance cost of different types of damage on the Swedish rail infrastructure. The engineering method is good at predicting damage from traffic, while the economic method is suitable for establishing a relationship between damage and cost. We exploit the best features of both methods in a two-stage approach and demonstrate its applicability for rail infrastructure charging, based on a sample of 143 track sections comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The econometric results indicated that TS is the most expensive of the three mechanisms in terms of the maintenance cost, followed by RCF and AW. Öberg and Andersson (2009) developed a bottom-up track charging model, considering TS, TCF, AW, and RCF in the context of Swedish mainline traffic and vehicles; additional similar studies have also been conducted (Smith et al, 2015(Smith et al, , 2016.…”
Section: Quantification Of Track Deteriorationmentioning
confidence: 99%
See 2 more Smart Citations
“…The econometric results indicated that TS is the most expensive of the three mechanisms in terms of the maintenance cost, followed by RCF and AW. Öberg and Andersson (2009) developed a bottom-up track charging model, considering TS, TCF, AW, and RCF in the context of Swedish mainline traffic and vehicles; additional similar studies have also been conducted (Smith et al, 2015(Smith et al, , 2016.…”
Section: Quantification Of Track Deteriorationmentioning
confidence: 99%
“…However, the abnormal interaction between rolling stock and infrastructure, which could be caused by RSFs such as wheel flats, brake failure, and suspension faults, was not considered. More information concerning the influence of WR interface on track deterioration can be found in (Smith, 2003;Falomi et al, 2011;Halama et al, 2011;Liang et al, 2013;Ye et al, 2020a).…”
Section: Quantification Of Track Deteriorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, referring to Refs. [64,65], the track model is simplified as a co-running track with a form of 'rail ? track slab ?…”
Section: Vehicle-track Modelmentioning
confidence: 99%